BS EN ISO/IEC 19763-12 AMD 1. Information technology. Metamodel framework for interoperability (MFI). Part 12. Metamodel for information model registration. Alignment with Edition 4 of ISO/IEC 11179-3 (9th June 2023) - British Standards Institution,
No abstract available